2022
DOI: 10.1021/acsami.2c14107
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-Induced Quaternized Anthrone-Containing Poly(aryl ether ketone) Membranes with Low Area Resistance and High Ion Selectivity for Vanadium Flow Batteries

Abstract: A vanadium flow battery (VFB) is one of the most promising electrochemical energy storage technologies. However, membranes for VFBs still suffer from high cost or low conductivity and poor stability. Here, we report new quaternized anthrone-containing poly(aryl ether ketone) (QAnPEK) membranes for VFBs. QAnPEK membranes with moderate ion exchange capacity (1.26 mmol g–1) were swelling-induced in H3PO4 (50 wt %) to form wider ion transport pathways that significantly enhanced membrane conductivity (e.g., 0.49 Ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The capacity retention of the C-PyPEKK-90 and Nafion212 membranes at 160 mA cm –2 is summarized in Figure b. The C-PyPEKK-90 membrane exhibited a high-capacity retention rate (75.54%), about 1.9 times better than that of the Nafion212 membrane (39.22%) due to the high ion selectivity of the C-PyPEKK-90 membrane resulting in low vanadium ion crossover …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity retention of the C-PyPEKK-90 and Nafion212 membranes at 160 mA cm –2 is summarized in Figure b. The C-PyPEKK-90 membrane exhibited a high-capacity retention rate (75.54%), about 1.9 times better than that of the Nafion212 membrane (39.22%) due to the high ion selectivity of the C-PyPEKK-90 membrane resulting in low vanadium ion crossover …”
Section: Resultsmentioning
confidence: 99%
“…The C-PyPEKK-90 membrane exhibited a high-capacity retention rate (75.54%), about 1.9 times better than that of the Nafion212 membrane (39.22%) due to the high ion selectivity of the C-PyPEKK-90 membrane resulting in low vanadium ion crossover. 69 The in situ stability of C-PyPEKK and uncross-linked PyPEKK-90 membranes under strongly acidic and oxidative conditions was investigated. Uncross-linked PyPEKK-90 membranes and cross-linked C-PyPEKK membranes were immersed in 1.5 M VO 2 + in 3 M H 2 SO 4 for 9 months at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…59 Zhang et al reported 85.0% EE at 200 mA cm −2 for a quaternized anthrone-containing poly(aryl ether ketone) membrane. 65 More recently, a functionalized carbon black-modified sulfonated polyether ether ketone membrane displayed 80.0% EE at 200 mA cm −2 . 67 An ion-selective membrane constructed by incorporating graphitic carbon nitride nanosheets into a nonionic host matrix achieved 85.0% EE at 200 mA cm −2 .…”
Section: Single-cell Vrfb Performancementioning
confidence: 99%
“…For example, a benzimidazole-functionalized adamantanecontaining poly(aryl ether ketone) membrane exhibited an EE of 80.0% at 200 mA cm −2 59. Zhang et al reported 85.0% EE at 200 mA cm −2 for a quaternized anthrone-containing poly(aryl ether ketone) membrane 65. More recently, a functionalized carbon black-modified sulfonated polyether ether ketone membrane displayed 80.0% EE at 200 mA cm −2 67.…”
mentioning
confidence: 99%
“…As expected, the membrane shows an ultralow area resistance of 0.04 Ω cm 2 , much lower than those of previously reported nonperfluorinated membranes in VFBs (Figure c and Table S2). ,,,, In addition, the free-standing sub-10 μm membrane surprisingly demonstrates very high mechanical performance with a high tensile strength of 45.5 MPa due to its cross-linked network, superior to the Nafion 115 membrane (21.7 MPa). The cross-linked structure can also efficiently inhibit the transference of vanadium ions, achieving a low vanadium permeability of 5.97 × 10 –6 cm 2 h –1 .…”
Section: Introductionmentioning
confidence: 99%